Photostability of organic electro-optic polymer under practical high intensity continuous-wave 1550 nm laser irradiation. (17th September 2021) - Tominari, Yukihiro; Yamada, Toshiki; Kaji, Takahiro; Yamada, Chiyumi; Otomo, Akira
Abstract: Information on the photochemical stabilities of organic electro-optic (EO) polymers under laser irradiation at 1550 nm, in the optical communication wavelength band (C-band), is crucial for understanding the long-term stability of various optical devices that employ EO polymers and providing guidelines for extending the devices' lifetime. Thus, in this study, we constructed a pump–probe photostability evaluation system with an intensity of as high as 1.49 MW cm −2 and intensively investigated the photochemical stability of an EO polymer at 85 °C under irradiation by using a continuous-wave (CW) 1550 nm laser. We found that the photobleaching rate was proportional to the square of the pump intensity, suggesting that the dominant photodegradation pathway was associated with two-photon absorption. Our findings provide new insights into a photobleaching mechanism under non-resonant CW laser excitation conditions.